THEORETICAL STUDY OF THE ADSORPTION OF CATECHIN, QUERCETIN AND GALLIC ACID MOLECULES ON IRON AS POTENTIAL CORROSION INHIBITORS: COMPUTATIONAL SIMULATION - H. Córdova, Carlos (2022)
The study of molecules extracted from natural products is becoming increasingly important for the evaluation of different properties such as antioxidant or corrosion inhibitor. The present work presents the computational studies carried out to evaluate mainly three polyphenolic molecules, such as catechin, quercetin and gallic acid, in their potential antioxidant activity, as well as the possible interactions with an iron substrate simulating its cubic crystalline structure centered on the body. The polyphenolic molecules were studied by computer simulation using Density Functional Theory (DFT). They were optimized by the Gaussian 09 software, by the Density Functional Theory (DFT) calculations, with the B3LYP functional (three hybrid parameters of the Becke and Lee-Yang-Para functional) and the set of bases 6-31G. The Vesta software was used to design the iron unit cell. Chemcraft software was used to construct a network of iron cells simulating a low carbon steel surface.Spartan software was used to calculate the Mulliken charge density distribution of the polyphenolic molecules. In the computational calculations, the energetic gaps of the molecules of gallic acid (-4.71 eV), catechin (-4.30eV) and quercetin (-3.73Ev) will be compared.